An M/G/1 Retrial G-queue with Multiple Working Vacation and a Waiting Server - Pazhani Bala Murugan, S.; Keerthana, R. (Communications in Mathematics and Applications, 2022)
An M/G/1 retrial G-queue with multiple working vacation and a waiting server is taken into consideration in this study. Both the retrial times and service times are assumed to follow general distribution and the waiting server follows an exponential distribution. During the working vacation period customers are served at a lesser rate of service. Before switching over to a vacation the server waits for some arbitrary amount of time and so is called a waiting server. We obtain the PGF for the number of customers and the mean number of customers in the invisible waiting area which is acquired by utilizing the supplementary variable technique. We compute the waiting time distribution. Out of interest a few special cases are conferred. Numerical outcomes are exhibited.